2022
DOI: 10.7189/jogh.12.04063
|View full text |Cite
|
Sign up to set email alerts
|

Availability of two essential medicines for mental health in Bangladesh, the Democratic Republic of Congo, Haiti, Nepal, Malawi, Senegal, and Tanzania: Evidence from nationally representative samples of 7958 health facilities

Abstract: Background Access to effective mental health services in low- and- middle income countries (LMICs) is limited, leading to a substantial global treatment gap. Amitriptyline, an anti-depressant, and diazepam, an anxiolytic drug, are classified as essential medications by the World Health Organization (WHO). They are the only psychotropic medications whose availability in health facilities is documented as part of Service Provision Assessment surveys. Our objective was to characterize the availabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
2
1
Order By: Relevance
“…Other studies have shown that individuals often prefer seeking care from traditional healers, even though they seek treatment for conditions such as epilepsy in healthcare facilities [ 1 , 30 ]. The availability of medicines like diazepam in our study contrasts with reports of low availability in other low- and middle-income countries (LMICs), highlighting the slow progress some countries are making in integrating mental health services into primary care in LMICs [ 31 , 32 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Other studies have shown that individuals often prefer seeking care from traditional healers, even though they seek treatment for conditions such as epilepsy in healthcare facilities [ 1 , 30 ]. The availability of medicines like diazepam in our study contrasts with reports of low availability in other low- and middle-income countries (LMICs), highlighting the slow progress some countries are making in integrating mental health services into primary care in LMICs [ 31 , 32 ].…”
Section: Discussioncontrasting
confidence: 99%
“…20 The availability of Diazepam 5 mg tablet was higher than in seven low-and lower-middle-income countries 25 and also other countries like Gambia, 23 Jordan, 24 and China. [26][27][28] Generally, the availability of sodium valproate, carbamazepine, phenytoin, phenobarbitone, and diazepam in this study was higher than availability in 46 countries with different income levels. 29 Addis Ababa is the capital city of Ethiopia, where many health facilities and specialized health services are provided.…”
Section: Discussionmentioning
confidence: 54%
“…This was higher than the average availability of all WHO regions of the world 22 and also higher than the average availability in each different income‐level categorized countries, 22 Zambia, 16 Madagascar, 17 Jordan, 24 and Cambodia 20 . The availability of Diazepam 5 mg tablet was higher than in seven low‐ and lower‐middle‐income countries 25 and also other countries like Gambia, 23 Jordan, 24 and China 26–28 . Generally, the availability of sodium valproate, carbamazepine, phenytoin, phenobarbitone, and diazepam in this study was higher than availability in 46 countries with different income levels 29 …”
Section: Discussionmentioning
confidence: 90%
“…24 The problem arises when there is a need to switch medication in each group, since the availability of the second chosen medicine was mostly very low. The availability of Amitriptyline 25 mg tablet and Diazepam 5 mg tablet was higher than seven low and lower-middle income countries, 25 and also other countries like Gambia 23 and China. [26][27][28] The overall availability of LPG fluoxetine 20 mg capsules was 53.2%, with 42.9% in the public sector and 80% in the private sector.…”
Section: Discussionmentioning
confidence: 83%